Is platelet to lymphocyte ratio predictive of preeclampsia? A systematic review and meta-analysis - Tianyong Qiang; Xiuqin Ding; Jiajia Ling; Meirong Fei (Taylor & Francis Group, 2023)
AbstractBackground To evaluate the value of the platelet-to-lymphocyte ratio (PLR) in predicting preeclampsia (PE) in pregnant women.Methods PubMed, EMBASE and Web of Science databases were searched for observational studies (cohort, case-control or cross-sectional) that reported pre-treatment maternal PLR values in women with and without PE. The analysis was done using a random effects model. Pooled effect sizes were reported as weighted mean difference (WMD) with 95% confidence intervals (CIs). Newcastle-Ottawa Scale (NOS) was used to evaluate the risk of bias.Results Twenty-five studies with 7755 patients were included in this meta-analysis. PLR was comparable in patients with PE and healthy pregnant women (WMD −2.97; 95% CI: −11.95 to 6.02; N = 16). Patients with mild (WMD −3.00; 95% CI: −17.40 to 11.41; N = 12) and severe PE (WMD −5.77; 95% CI: −25.48 to 13.94; N = 14) had statistically similar PLR, compared to healthy controls.Conclusions Our findings show similar PLR in PE and healthy pregnancies. PLR, therefore, may not be used to differentiate between PE and normal pregnancy or for assessing the severity of PE. The majority of included studies were case-control, potentially introducing bias, and we identified evidence of publication bias as well.